Evaluation of a newly developed oral and maxillofacial surgical robotic platform (KD-SR-01) in head and neck surgery: a preclinical trial in porcine models - Zhongkai Ma; Zhiyong Guo; Zhangfan Ding; Chang Cao; Jialu He; Heyi Tang; Yufei Hua; Jiawei Hong; Qiang Shen; Grace Paka Lubamba; Xiaoyi Wang; Zheng Yang; et al. (Nature Publishing Group, 2024)
Abstract Traditional open head and neck surgery often leaves permanent scars, significantly affecting appearance. The emergence of surgical robots has introduced a new era for minimally invasive surgery. However, the complex anatomy of the head and neck region, particularly the oral and maxillofacial areas, combined with the high costs associated with established systems such as the da Vinci, has limited the widespread adoption of surgical robots in this field. Recently, surgical robotic platform in China has developed rapidly, exemplified by the promise shown by the KangDuo Surgical Robot (KD-SR). Although the KD-SR has achieved some results comparable to the da Vinci surgical robot in urology and colorectal surgery, its performance in complex head and neck regions remains untested. This study evaluated the feasibility, effectiveness, and safety of the newly developed KD-SR-01, comparing it with standard endoscopic systems in head and neck procedures on porcine models. We performed parotidectomy, submandibular gland resection, and neck dissection, collected baseline characteristics, perioperative data, and specifically assessed cognitive workload using the NASA-TLX. None of the robotic procedures were converted to endoscopic or open surgery. The results showed no significant difference in operation time between the two groups (P = 0.126), better intraoperative bleeding control (P = 0.001), and a significant reduction in cognitive workload (P < 0.001) in the robotic group. In conclusion, the KD-SR-01 is feasible, effective, and safe for head and neck surgery. Further investigation through well-designed clinical trials with long-term follow-up is necessary to establish the full potential of this emerging robotic platform.